2022
DOI: 10.3390/nu14071471
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms in Autism Spectrum Disorder: A Systematic Review

Abstract: This systematic review aims to offer an updated understanding of the relationship between gastrointestinal symptoms (GIS) and autism spectrum disorder (ASD) in children and adolescents. The databases PsycINFO, Medline, Cinahl, and ERIC were searched using keywords, and relevant literature was hand-searched. Papers (n = 3319) were systematically screened and deemed eligible if they were empirical studies published in English since 2014 and measured the GIS of individuals with ASD who were under 18 years old. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 77 publications
1
44
0
1
Order By: Relevance
“…Hence, interest in the effect of special diets and nutrition on autism is increasing, particularly as a way to improve behavior, attention span, social interaction, and eye contact [ 4 ]. Many studies have shown that some children and adolescents with autism are on a gluten and casein free (GFCF) diet [ 5 , 6 ]. Graf-Myles et al reported that diet restrictions can impact dietary intake of cereals and dairy and may also lead to a lower intake of calcium and grains supplemented with folate in ASD group as compared to TD group [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, interest in the effect of special diets and nutrition on autism is increasing, particularly as a way to improve behavior, attention span, social interaction, and eye contact [ 4 ]. Many studies have shown that some children and adolescents with autism are on a gluten and casein free (GFCF) diet [ 5 , 6 ]. Graf-Myles et al reported that diet restrictions can impact dietary intake of cereals and dairy and may also lead to a lower intake of calcium and grains supplemented with folate in ASD group as compared to TD group [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, neurotypical children around the age of six often show a preference for certain foods and a rejection of others as a part of their developmental age [ 3 , 4 ]. Many influencing factors can affect an individual’s food choices, and studies suggest that eating disorders in autism may be one significant contributor to comorbidities such as gastrointestinal symptoms [ 2 , 5 , 6 ]. Additionally, some studies show that children with ASD have greater rates of overweight or obesity than typically developing (TD) ones, and this fact could be related to unusual dietary patterns and decreased opportunities for physical activity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are no studies reporting the use of the BRAVO wireless pH to evaluate GER in children with ASD. Also, guidelines for evaluation of gastrointestinal manifestations in children with ASD are not clear due to lack of evidence supporting the evaluation of ASD children with potential GER (21), and a recent systematic review emphasized the potential association between gastrointestinal symptoms and presence but not severity of ASD (22).…”
Section: Discussionmentioning
confidence: 99%
“…4 Children with ASD are at least three times more likely to experience co-occurring gastrointestinal symptoms, including constipation, diarrhea and abdominal pain, than neurotypical children. 5 Recent studies have confirmed differences in the composition of gut microbiota between ASD patients and neurotypical people. 6 Microbial communities play a central role in the maturation and development of the immune, neural and gastrointestinal systems and are also responsible for important metabolic pathways.…”
Section: Introductionmentioning
confidence: 91%